Quantifying the effects of antibiotic treatment on the extracellular polymer network of antimicrobial resistant and sensitive biofilms using multiple particle tracking - Lydia C. Powell (Nature Portfolio, 2021)
Abstract Novel therapeutics designed to target the polymeric matrix of biofilms requires innovative techniques to accurately assess their efficacy. Here, multiple particle tracking (MPT) was developed to characterize the physical and mechanical properties of antimicrobial resistant (AMR) bacterial biofilms and to quantify the effects of antibiotic treatment. Studies employed nanoparticles (NPs) of varying charge and size (40–500 nm) in Pseudomonas aeruginosa PAO1 and methicillin-resistant Staphylococcus aureus (MRSA) biofilms and also in polymyxin B (PMB) treated Escherichia coli biofilms of PMB-sensitive (PMBSens) IR57 and PMB-resistant (PMBR) PN47 strains. NP size-dependent and strain-related differences in the diffusion coefficient values of biofilms were evident between PAO1 and MRSA. Dose-dependent treatment effects induced by PMB in PMBSens E. coli biofilms included increases in diffusion and creep compliance (P < 0.05), not evident in PMB treatment of PMBR E. coli biofilms. Our results highlight the ability of MPT to quantify the diffusion and mechanical effects of antibiotic therapies within the AMR biofilm matrix, offering a valuable tool for the pre-clinical screening of anti-biofilm therapies.